NU: Islam Tradisional dan Modernitas di Indonesia - Azyumardi Azra (Studia Islamika, 1997)
As stated by Abdurrahman Wahid in his introduction, the book under discussion is the first one written in English, not in the Indonesian language, that discusses the Nahdatul Ulama (NU). This is of course very surprising, since the NU is one of the largest Muslim organizations in Indonesia.DOI: 10.15408/sdi.v4i4.770